PERSONALITY CONGRUENCY WITH PROGRAMME MAJORS AND ITS RELATIONSHIP TO KUTKM STUDENTS’ ACADEMIC PERFORMANCE - Norida, Abdullah; Ahmad Rozelan, Yunus; Hafzan, Ariffin (2006)
This study was conducted to determine the congruency between the type of student personality with their major academic program based on Holland’s Personality-Environment Congruence Theory among first degree student of Kolej Universiti Teknikal Kebangsaan Malaysia. This study also to determine the relationship among the congruency of personality with the academic performance. The subjects of the study are 746 student who were selected using group random sampling from a total of 1103 student in the first semester of third year of Bachelor Degree Program. The instrument was used in this study is Self Directed Search (SDS). The statistical tests used to analyze the data are Environment Assessment Technique (EAT), Wiggins’s Index of Congruence and Spearman Rho (rs) at the .05 significant level. The finding showed that there was a significant congruency between the personality of the students and their major academic program for the group of BEKP, BEKC, BMCT, BMCA and BMCS. There was no significant congruency between personality of the students and their major academic program for the group of BEKE, BMFP, BMFR, BMFA, BITD, BITM, BITS, BITC, BENC, BENT and BENE. The finding also showed that there was a significant relationship between congruency personality with academic performance for all academic program excepted for program BENC, BENT, and BENE. The outcome of the study also showed that some of the students had chosen the major academic program is congruence with their personality and some of them are not. In view of the finding, few implications and recommendation were put forward.